Optimization of Binluh Bhabinkamtibmas Polres Pekalongan in Effort to Prevent Drug Abuse - Situmorang, Daniel Edward H (Advances in Police Science Research Journal, 2024)
This final project is based on the importance of the role of bhabinkamtibmas in preventing drug abuse. The formulation of the problems discussed in this Final Project is about the condition of the role of bhabinkamtibas in efforts to prevent drug abuse through the binluh method, the condition of the community when applying the binluh method in an effort to prevent drug abuse, and efforts to strengthen the binluh bhabinkamtibmas method in an effort to prevent drug abuse. The purpose of writing this Final Project is to find out the correlation and relevance between the binluh carried out by bhabinkamtibmas and the prevention of drug abuse by discussing in terms of the role, the method of binluh, as well as efforts to optimize the binluh bhabinkamtibmas of the Pekalongan Police in an effort to prevent drug abuse. The research method used is a qualitative research method with data analysis techniques in the form of Focus Group Discussion (FGD) with several related parties, interviews, observations, and document studies with a theoretical approach, management theory. The results of this study show that the role of Bhabinkamtibmas with the binluh method shows positive results in the context of preventing drug abuse, but there are still shortcomings in various aspects of creativity in implementing the binluh method. Therefore, it is necessary to guide and strengthen the competence of bhabinkamtibmas, budget and supporting facilities and infrastructure, as well as creativity from bhabinkamtibmas in the application of the binluh method in the community so that later people can understand the prevention of drug abuse clearly and bhabinkamtibmas to be effective and creative when carrying out binluh activities. drugs at the Pekalongan Police.